Morphophysical reaction of Hordeum vulgare to the influence of microbial preparations - Rassokhina, I. I.; Platonov, A. V.; Laptev, G. Y.; Bolshakov, V. N. (Regulatory Mechanisms in Biosystems, 2020)
Bacterial preparations contribute to the digestion of mineral nutrition, have antifungicidal activity, increase the grain productivity and biomass of cultivated crops. We studied the influence of microbiological preparations developed on the basis of microorganisms Bacillus subtilis and Lactobacillus buchneri on the growth processes, photosynthetic parameters and grain productivity of barley (Hordeum vulgare L.) of Sonet variety. The experiments were performed in 2019 in the North-West of the Russian Federation. The biological preparations were introduced by soaking seeds and treatment of the plants in the phase of third leaf with solutions of the preparations in the concentration of 1 mL/L. The laboratory surveys revealed the positive effect of the biological preparations on germination rate and energy of germination of seeds. Field trials were conducted on micro plots in six replications. During field experiments, we determined that introduction of biological preparations led to significant increase in the leaf area in the experimental plants (to 64.5%), increase in average daily growth gains (to 82.9%) and accumulation of biomass (to 73.1%). Somewhat higher efficiency was exerted by the biological preparation developed on the basis of a strain of L. buchneri. Perhaps, such effect takes place due to higher activity of pigment units of phytohormones of the auxin group. In our opinion, biological preparations accelerate the completion of the ontogenesis phases, thus the plants more rapidly achieve their genetically programmed sizes and transform to the stage of ear-formation. The studied biological preparations increased the coefficient of agricultural use of plants, and grain productivity of barley by up to 15.8%, and nutritional value remained. Microbial preparations on the basis of B. subtilis and L. buchneri exhibited efficiency, and their trials shall be continued on other crops on industrial scales.